A Urachal Cyst Case with Painful Mass Locates at Ileal Mesentery - Selahattin Koray Okur; Hüseyin Pülat; Oktay Karaköse; Ismail Zihni; Kazım Çağlar Özçelik; Hasan Erol Eroğlu (Case Reports in Surgery)
Urachal cyst is an unusual clinical condition, which is usually asymptomatic. In some adult cases, it may lead to complications. The cyst is between umbilicus and urinary bladder. It is diagnosed via ultrasonography and computed tomography. However, in some cases, the diagnosis is made by means of surgical exploration and histopathological evaluation. In this paper, we report a case of a 17-year-old female presenting with painful abdominal mass. At the first evaluation, the case was diagnosed as a mesenteric cyst because the mass located in the mesentery, and final histopathological report revealed the urachal cyst.